Statistical abstract of the United States. - United States. Bureau of the Census (Washington U.S. Govt. Print. Off., 1879)
Annual
Issued 1878-1902 by the Bureau of Statistics (Treasury Dept.); 1903-11 by the Bureau of Statistics (Dept. of Commerce and labor); 1912-37 by the Bureau of Foreign and Domestic Commerce.
The 7th-8th editions combined in one issue; 66th ed. covers period 1944-45.
Keywords: United States -- Statistics